The impact of customer satisfaction on purchase intention in Malaysian takaful industry - Abu Hassan, Lailatul Faizah; Wan Jusoh, Wan Jamaliah; Hamid, Zarinah (2015)

(untitled)
To date the study of customer satisfaction and purchase intention have dominated the services literature. This study is aimed to investigate the impact of customer satisfaction on purchase intention among Takaful participants in Malaysia. A self-administered questionnaire is distributed to eight Takaful companies in Malaysia as a study setting for this study. Out of the total 600 distributed questionnaires 390 were finally selected for data analyses. It is expected that findings from this study will contribute to the existing literature to both theoretical and managerial approaches in order to better understand the pattern of customer satisfaction and purchase intention in Takaful industry settings.